Analisis Kebutuhan Pengembangan Media Game Scratch dengan Pendekatan TPACK pada Muatan IPA Kelas IV SD - Ananda Salsabillah Zahra; Herlina Usman; Prayuningtyas Angger Wardhani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Education is a crucial aspect in the national development based on the values of Pancasila and the 1945 Constitution. The digital era of the 21st century demands the integration of technology in education, one of which is through the TPACK approach that combines technological knowledge, content, and pedagogy. This article explores the need for developing Scratch-based educational games media for science learning in fourth-grade elementary school. Through the research and development (R&D) approach using the ADDIE model, this study aims to evaluate the needs, identify barriers, and provide recommendations for the use of Scratch educational games media in science learning. The survey results show that the majority of students find science learning enjoyable and support the use of instructional media, especially games and animations. However, there is still a need to enhance the use of media in teaching by teachers. By utilizing Scratch-based educational games media, science learning in elementary school can become more interactive, engaging, and effective, preparing students to face educational challenges in the current digital era.